Population genetic diversity of Huperzia chinensis (Herter ex Nessel) Ching. in Northwest region of Vietnam revealed by ISSR and SCcoT markers - Ngoc Trieu, Le; Van Tien, Tran; Thai Vinh, Tran; Van Duy, Nong (Vietnam Journal of Biotechnology, 2022)
Genetic diversity of natural Huperzia chinensis population in Northwest region of Vietnam was analyzed based on the DNA fingerprint data induced by ISSR and SCoT methods separately and combined data from both methods. The genetic diversity parameters and genetic distances among individuals based on SCoT technique were higher than ISSR technique [expected heterozygousity (HeS) was 0.2812; Shannon index (IS) was 0.4153; Percentage of polymorphic bands (PPBS) was 75.44%; Genetic similarity coefficients (GSCsS ) were in range of 0.561 - 0.947 with the average value (AGSCS) of 0.758 revealed by SCoT technique compared to HeI was 0.2394; II was 0.3515; PPBI was 60.87%, GSCsI were 0.551 - 0.986 and AGSCI was 0.860 revealed by ISSR technique. Combined data showed that genetic diversity level of investigated population (He was 0.2583; I was 0.3804; PPB was 67.46%, higher than genetic diversity level of Huperzia serrata population in the same distribution area which was previously evaluated by the same markers. Combined data also indicated the genetic similarities among individuals (GSCs) were 0.579 - 0.960 with the average (AGSC) of 0.814. ISSR method reflected more loci in the investigated plants than SCoT method but SCoT method could differentiate the tested samples better and reflects genetic diversity at higher level than ISSR method.